2016
DOI: 10.5306/wjco.v7.i5.387
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating lymphocytes in triple negative breast cancer receiving neoadjuvant chemotherapy

Abstract: AIMTo determine influence of neoadjuvant-chemotherapy (NAC) over tumor-infiltrating-lymphocytes (TIL) in triple-negative-breast-cancer (TNBC).METHODSTILs were evaluated in 98 TNBC cases who came to Instituto Nacional de Enfermedades Neoplasicas from 2005 to 2010. Immunohistochemistry staining for CD3, CD4, CD8 and FOXP3 was performed in tissue microarrays (TMA) sections. Evaluation of H/E in full-face and immunohistochemistry in TMA sections was performed in pre and post-NAC samples. STATA software was used an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 22 publications
6
37
1
Order By: Relevance
“…The prognostic impact of TIL before neoadjuvant treatment (pre-NAC TIL) has been extensively reported, particularly in TNBC [15,16,18,19], but was not confirmed in our study in terms of association with EFS. Notably, the pre-NAC TIL rate in our study was low.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The prognostic impact of TIL before neoadjuvant treatment (pre-NAC TIL) has been extensively reported, particularly in TNBC [15,16,18,19], but was not confirmed in our study in terms of association with EFS. Notably, the pre-NAC TIL rate in our study was low.…”
Section: Discussioncontrasting
confidence: 85%
“…Pelekanou et al [22] showed, with a cohort of 58 patients whose15.5% with TNBC (9 patients), that TIL increase after NAC was associated with improved recurrence-free survival [22]. Four other studies reviewed the impact of post-NAC TIL but only two in TNBC exclusively [18,19,24,25]. Hamy et al [25], in a series of 716 breast cancers treated with NAC, showed that high post-NAC TIL levels were associated with aggressive tumor characteristics and with impaired EFS in HER2-positive breast cancers but not in luminal tumors or TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the 4 patients (3 low TILs; 1 high TILs) who achieved a cCR [estrogen receptor (ER) + /HER2 -, 2 patients; ER -/HER2 + , 2 patients] showed that the TIL score had no prognostic value in MBC. According to previous reports, the TIL score is a prognostic marker in HER2 + breast cancers (20), as well as triple-negative breast cancers (TNBC) in the both neoadjuvant and adjuvant settings (11,21,22). Because all TNBC patients in this study showed low TILs, the relationship between prognosis of TNBC patients and high TILs could not be evaluated.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we found that the high TIL group had a more negative threshold Ki-67 level (<14%), and this result verified that TNBC patients with high TIL levels probably have low Ki-67 levels. Then, the tumors have less malignant cell proliferation, and they exhibit a positive reaction to neoadjuvant chemotherapy (37,38).…”
Section: Discussionmentioning
confidence: 99%